Effect of differential irrigation regimes on potato (Solanum tuberosum) yield and post-harvest post-harvest attributes* - KUMAR, SATYENDRA; ASREY, RAM; MANDAL, GOUTAM (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2002-03 and 2003-04 to 1.70 45 5 1 6 5.36 13.28 1.115 evaluate the role of differential irrigation regime on growth, LSD 0.51 0.61 0.03 1 yield and post-harvest attributes of potato (Solanum tubersum L.) Plant height, biomass and tuber yield increased with increase in irrigation. The highest tuber yield was obtained in the irrigation regime of 1.20 Ep while the highest irrigation water-use efficiency was found in 0.80 Ep. Preferable grade of tuber (> 28 mm size) decreased with decrease in rriigation level from 1.20 to 0.60 Ep. Specific gravity and starch percentage in tuber increased with increase in irrigation. Therefore potatoes should be irrigated at 1.20 Ep for higher yield and better quality. However if water availability is limited 0.80 Ep would be most appropriate for scheduling irrigation.